The 2021 Update on Pressure Injuries: A Review of the Literature. (August 2022) - Saindon, Kelley; Nguyen, Tran D.; Berlowitz, Dan R.
Abstract : GENERAL PURPOSE: To provide a review of the recent literature on the epidemiology and treatment of pressure injuries (PIs). TARGET AUDIENCE: This continuing education activity is intended for physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES/OUTCOMES: After participating in this educational activity, the participant will: 1. Identify risk factors for developing PIs. 2. Differentiate factors that could affect the healing of PIs. 3. Select strategies that have an impact on the development of PIs. ABSTRACT: Keeping up with the literature on pressure injuries is always a challenge for busy clinicians. In this article, the authors summarize six important articles published in 2021. Articles cover a range of topics including epidemiology, treatment, precision medicine, nurse staffing, and patient preferences for care. For each article, a description of the study results is provided along with a comment on why the results are important. This information is intended to help clinicians incorporate new data into their clinical practice.